The Financial Aspects of Innovative Development of the Railway Transport in Ukraine - Kravchenko, Olha; ., . (International Journal of Engineering and Technology, 2018)
The implementation of the strategy of re-industrialization of national economies is now the main trend in both Europe and Asia. In this context, railways are of great importance, as a mode of transport, capable of carrying large volumes of cargo and passengers with a sufficiently high speed. Special attention is paid to the innovative development of transport corridors connecting Europe and Asia to a single transport network. Mainly this paper is devoted to the financial aspects of the development of Ukrainian railway infrastructure, which has a significant transit potential. It is shown that underfunding of renewal of fixed assets of railways leads not only to the intensification of current problems, but to the formation of problems that will have a decisive influence in the future. The high cost of projects related to the innovative development of the railway infrastructure necessitates the attraction of private capital. The types of public-private partnership models as a mechanism for investment financing are considered. It has been determined that for the railway transport the most feasible are the BOT (build-operate-transfer) and BOOT (built–own–operate–transfer) models, which allow to ensure the innovative development of strategic infrastructure sites and maintain its integrity, by keeping it in state ownership.